2017
DOI: 10.5536/kjps.2017.44.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Meat Qualities and Functional Properties of Broiler and Spent Layers Slaughtered at Different Ages

Abstract: This study was conducted to identify the quality and functional properties of meat and meat batter among commercial broilers and two different ages of spent layers. Breast and whole leg meat samples were prepared from the broilers and spent layers to compare meat quality traits: Commercial broiler (Arbor Acre; 6-week-old) and two different ages of spent layers (Hy-Line; 70 and 95-week-old). Three types of meat batters containing breast meat as 50% of total ingredients were also prepared to analyze processing q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…This is similar to the results of a study by Kadıoğlu et al [ 23 ], who studied the color of spent chicken meat and reported more redness in the thigh than in the breast. Yellowness was significantly higher in the SB group than in the other groups, which was similar to the findings of Baek et al [ 20 ], which showed that yellowness increased with age.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is similar to the results of a study by Kadıoğlu et al [ 23 ], who studied the color of spent chicken meat and reported more redness in the thigh than in the breast. Yellowness was significantly higher in the SB group than in the other groups, which was similar to the findings of Baek et al [ 20 ], which showed that yellowness increased with age.…”
Section: Resultssupporting
confidence: 90%
“…In addition, the spent hen showed a significantly lower pH than the broiler, which is thought to be due to the decrease in the water content in the muscles with increasing age. Beak [20] et al showed the same results as in this study, saying that the pH decreased as the age of the laying hen increased.…”
Section: Ph and Colorsupporting
confidence: 86%